Reduced Rivaroxaban Dose Versus Dual Antiplatelet Therapy After Left Atrial Appendage Closure: ADRIFT a Randomized Pilot Study. (July 2020) - Duthoit, Guillaume; Silvain, Johanne; Marijon, Eloi; Ducrocq, Grégory; Lepillier, Antoine; Frere, Corinne; Dimby, Solohaja-Faniaha; Popovic, Batric; Lellouche, Nicolas; Martin-Toutain, Isabelle; Spaulding, Christian; Brochet, Eric; et al.
Abstract : Background: Percutaneous left atrial appendage closure (LAAC) exposes to the risk of device thrombosis in patients with atrial fibrillation who frequently have a contraindication to full anticoagulation. Thereby, dual antiplatelet therapy (DAPT) is usually preferred. No randomized study has evaluated nonvitamin K antagonist oral anticoagulant after LAAC, and we decided to evaluate the efficacy and safety of reduced doses of rivaroxaban after LAAC. Methods: ADRIFT (Assessment of Dual Antiplatelet Therapy Versus Rivaroxaban in Atrial Fibrillation Patients Treated With Left Atrial Appendage Closure) is a multicenter, phase IIb study, which randomized 105 patients after successful LAAC to either rivaroxaban 10 mg (R 10, n=37), rivaroxaban 15 mg (R 15, n=35), or DAPT with aspirin 75 mg and clopidogrel 75 mg (n=33). The primary end point was thrombin generation (prothrombin fragments 1+2) measured 2 to 4 hours after drug intake, 10 days after treatment initiation. Thrombin-antithrombin complex, D-dimers, rivaroxaban concentrations were also measured at 10 days and 3 months. Clinical end points were evaluated at 3-month follow-up. Results: The primary end point was reduced with R 10 (179 pmol/L [interquartile range (IQR), 129–273], P <0.0001) and R 15 (163 pmol/L [IQR, 112–231], P <0.0001) as compared with DAPT (322 pmol/L [IQR, 218–528]). We observed no significant reduction of the primary end point between R 10 and R 15 while rivaroxaban concentrations increased significantly from 184 ng/mL (IQR, 127–290) with R 10 to 274 ng/mL (IQR, 192–377) with R 15, P <0.0001. Thrombin-antithrombin complex and D-dimers were numerically lower with both rivaroxaban doses than with DAPT. These findings were all confirmed at 3 months. The clinical end points were not different between groups. A device thrombosis was noted in 2 patients assigned to DAPT. Conclusions: Thrombin generation measured after LAAC was lower in patients treated by reduced rivaroxaban doses than DAPT, supporting an alternative to the antithrombotic regimens currently used after LAAC and deserves further evaluation in larger studies. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03273322. Abstract : Supplemental Digital Content is available in the text.